O mentir pró-social em escolares: influências de idade, contexto social e consequências - Arruda, Daiane Araujo de (2018)
Lying with the purpose of gaining social acceptance is called prosocial lying. It serves to avoid embarrassment, to preserve privacy and affective bonds or even to escape from an embarrassing situation. Recent studies on prosocial lying have shown that children's assessments of this behavior vary depending on the social environment in which the interaction occurs and on the consequences of lying. Following this direction, the goal of the present study was to investigate how 7-, 9- and 11-years-old children evaluate prosocial lying in two experiments. In both experiments, participants heard stories during which the protagonist would either tell a prosocial lie; tell the truth and hurt the feelings of one friend; slander; or praise a friend. After hearing each story, children were asked to rate how good or bad the character's behavior was. In Experiment 1, participants heard eight stories, four taking place in a public setting and four in a private setting, thus creating a possibility to analyze whether children take into account the environment or social context to assess the behavior of others. In Experiment 2, children also heard eight stories; in four of them, the choice of the character would bring an important consequence to the other person in the future, whereas in the other four stories, for the consequence would be provided in the present moment. Sixty-nine children aged 7, 9 and 11 participated in Experiment 1; in Experiment 2, 72 children from the same three age groups. Results from Experiment 1 show that older children, more specifically 11-year-olds, considered that a blunt truth is better when spoken in a private setting than in a public setting, but there was no effect of environment when they evaluated prosocial lying. In Experiment 2, 11-year-olds rated a blunt truth more positively than a prosocial lie, however, the consequence of the choice made did not affect their assessments. Nevertheless, 11-year-olds rated more negatively lying when the consequence came later than when the consequence immediately followed the interaction, suggesting that these children were thinking about the possibility of the listener having problems later. The present work makes an important contribution to research on prosocial lying and, more comprehensively, research on moral development and cultural effects, in particular, by providing new evidence on the role of contextual variables for moral evaluation of lies and truths in a sample of Brazilian children.